Germination percentage and vitamin A and E content of hydroponic fodder tamarind seeds due to different amounts of watering - Wea, Redempta; Ninu, Andy Yumina; Suek, Ferdinan Suharjono; Malawati, Ima; Anugrah, Dedet Septian Graha; Koten, Bernadete Barek (Fakultas Peternakan Universitas Papua, 2024)
If the feed meets human needs, efforts will be made to find alternative feed by utilizing waste. One of them is the use of tamarind seeds using hydroponic fodder technology. The research aimed to examine the effect of different amounts of water watering in tamarind seed hydroponic fodder on the germination percentage and vitamin A and E content. The research was conducted in Matani, Penfui District, Regency, in 2024. The research used tamarind seeds originating from the mainland area of Timor. The research used a Completely Randomized Design (CRD), with four treatments for the amount of watering, namely P1 = Number of waterings (NoW) 10 ml, P2 = NoW 20 ml, P3 = NoW 30 ml, P4 = NoW 40 ml and six replications and there were 154 g or 100 seeds per container. Variables include germination percentage and tamarind seed fodder's vitamin A and E contents. Analysis of Variance (ANOVA) and Duncan's advanced test were used. The results showed that the amount of watering had a very significant effect (P<0.01) on the germination percentage and Vitamin A and E content, and the best amount of watering was 30 ml/day three times/day. In conclusion, the germination percentage and levels of vitamins A and E are influenced by the amount of watering, with the best watering amount being 30ml/day, so it is recommended that its use be tested on livestock.